Sources of repression, aggression and liberation in Erich Fromm and Herbert Marcuse - Aksoy Ozansü, Esen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
Why humans are the only species that kills systematically? What are the sources of aggression? What are the unconscious mechanisms through which repression of instincts leads to an increase in aggression? How do social institutions in an alienated society affect the human soul? In which ways do these institutions limit the possibilities for self-realization? How can a non-repressive society be constructed? To answer these questions, I have analyzed the theories of Erich Fromm and Herbert Marcuse. They both make a synthesis of Freud’s account of repression and Marx’s account of alienation. Whereas Freud claims that aggression is the inevitable result of repression, which increases with civilization, Fromm and Marcuse make a critique of capitalism to reveal how the current social system transforms human nature. For Freud, with the development of civilization, there was an inevitable tradeoff between freedom and security, which progressed in the same context with the repression of the Pleasure Principle by the Reality Principle. In contrast, Fromm’s distinction between benign (self-preservation) and malign (harm another being willingly) aggression and Marcuse’s distinction between Basic Repression and Surplus Repression provide useful theoretical tools to overcome the pessimism of Freud regarding the possibilities of liberation. Whereas Fromm analyses the specific social character shaped by capitalism, Marcuse emphasizes the specific Reality Principle of capitalism (Performance Principle) to explain the social and psychological dynamics behind alienation. Fromm’s account of existential passions and Marcuse’s notion ofnegativity (power to negate) provide us important tools to envision the possibilities of liberation from a repressive social order.